Association of Overactive Bladder With Hypertension and Blood Pressure Control: The Multi-Ethnic Study of Atherosclerosis (MESA). (26th April 2021) - Akbar, Aelia; Liu, Kiang; Michos, Erin D; Bancks, Michael P; Brubaker, Linda; Markossian, Talar; Durazo-Arvizu, Ramon; Kramer, Holly
Abstract: BACKGROUND: The sudden urge to urinate, also known as overactive bladder (OAB), may reflect higher sympathetic activity and associate with higher blood pressure (BP). METHODS: This cross-sectional analysis utilized data from sixth follow-up exam (2015–2016) of Multi-Ethnic Study of Atherosclerosis to examine the association of OAB with systolic (SBP) and diastolic blood pressure (DBP) levels, hypertension, and BP control. Information on urinary symptoms was obtained with the International Consultation on Incontinence Questionnaire (ICIQ). Sex-stratified regression models were constructed to examine differences in BP, hypertension prevalence, and BP control while adjusting for demographic factors, comorbidities, and medication use. RESULTS: Among the 1, 446 men and 1, 628 women who completed the ICIQ (mean age 73.7 years [SD 8.4]), OAB was present in 31.6% of men and 38.9% of women. With no antihypertensive medication use, OAB was not associated with SBP or DBP in both men and women after adjusting for covariates. However, among the 894 men and 981 women on antihypertensive medication, OAB was associated with higher SBP among men (4.04 mm Hg; 95% confidence interval [CI] 1.02, 7.06) but not among women (−0.67 mm Hg; 95% CI −3.79, 2.46) while DBP did not differ by OAB presence in men or women. In addition, OAB was also associated with lower odds of BP control among men (odds ratio [OR] 0.69; 95% CI 0.49, 0.96) but not women (OR 0.96; 95% CI 0.71, 1.30). CONCLUSIONS: Among men, OAB is associated with lower odds of BP control which suggests that OAB may impede hypertension management. Graphical Abstract: